IMPACT OF INCENTIVES AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE IN TECHNICAL SERVICE UNIT REGIONAL INCOME MANAGEMENT BANDAR JAYA REGION IV - Trisnowati Josiah (Saburai International Journal of Social Sciences and Development, 2021)
This study aims to determine the effect of incentives and work motivation on performance. The Hypothesis in this study is that incentives and work motivation are either partially or simultaneously on performance. The sample used in this study amounted to 36 employees. Data collection techniques include observation, documentation, and questionnaires. The data analysis method used a quantitative approach with the help of SPSS version 21.0 statistical tools, including the calculation of the validity test, reliability test, regression test, t-test, F test, and coefficient of determination test.The results of testing the Hypothesis of the effect of incentives on performance partially show that incentives positively affect performance with a contribution of 50.6%. The implication that can be conveyed is that the policy of providing incentives at the Regional Technical Service Unit for Regional Revenue Management Region IV Bandar Jaya needs to be reviewed because so far it has not fulfilled the element of justice; giving awards to employees such as the coronation of "achievement employees" which is held every certain period; it is necessary to apply a “Reward and Punishment” system.